Effect of trauma on mental health - Dr M. Qadeer, Fungrish, Kiran Riaz, kinza Muzaffar (International Research Journal of Arabic and Islamic Studies, 2023)
Trauma is an important aspect affecting mental health, especially if trauma comes from adverse childhood experiences (ACE) (Brewin et al., 1996). The current article immerses in the strong influence of trauma on psychological health and focuses on exposing traumatic events during childhood has permanent consequences for emotional regulation and mental health overall. Trauma, especially the child's trauma, derails typical emotional processing, resulting in emotional dysregulation expressed by increased sensitivity, impulsiveness and difficulty of controlling emotions. Individuals with a last history of ACE are exposed to increased risk of developing mental disorders such as anxiety, depression and post -traumatic stress disorder (PTSD)(Teicher & Samson, 2016). Flashbacks, the most disturbing feature of PTSD, are disturbing, living memories of traumatic experiences that can be cured by harmless stimuli, which further worsens emotional instability. The chronic course of these symptoms really worsens the daily functioning and quality of life. In addition, emotional dysregulation caused by trauma can also lead to a maladaptive style of management, such as drug abuse, which further complicates mental health. Recognition of connection between trauma, emotional dysregulation and flashbacks is important when determining effective interventions that can facilitate the recovery and resistance of mental health. Trauma-informed therapies like cognitive-behavioral therapy (CBT) and eye movement desensitization and reprocessing (EMDR) have been found to be useful in managing symptoms of trauma as well as in improving emotional regulation. This article emphasizes the need for early intervention and full mental health care to reduce the negative impact of trauma and enhance psychological outcomes(Cloitre et al., 2005).